Enacting Occupation-Based Practice: Exploring the Disjuncture between the Daily Lives of Mothers with Rheumatoid Arthritis and Institutional Processes. (October 2014) - Prodinger, Birgit; Shaw, Lynn; Stamm, Tanja; Rudman, Debbie Laliberte
Introduction: Occupation-based approaches are a hallmark of excellence in occupational therapy practice. This article focuses on the disjuncture between how women with rheumatoid arthritis go about their daily lives, that is to say their occupations, and what is addressed during routine visits at a specialized rheumatology outpatient clinic. Method: Institutional ethnography was employed as a method of inquiry to identify the occupations and related issues that were or were not accounted for in health records and addressed within institutional processes. Interviews and participant observations were conducted with seven women with rheumatoid arthritis who were mothers. Hospital records were analysed as texts mediating between the women's daily lives and the rheumatology outpatient clinic. Findings: The analysis revealed that despite the diversity in the ways that the women managed their daily lives, the things that they did were viewed, understood, and addressed only within the boundaries of the standardizing relations that ruled practice in this clinical setting. Institutional processes grounded in biomedical concepts such as functional status or disease activity, as well as clinical assessments that depict these concepts, both shape and limit opportunities for occupational therapists to advance and enact occupation-based practice. Conclusion: In this setting, the complexity of the participants' daily lives and the occupations they engage in remain unaddressed.